KONSTRUKSI PEMIKIRAN ISLAM M. ARKOUN; KRITIK TERHADAP NALAR ISLAM DAN NALAR MODERN - Rahman, Arif Aulia (STAIN Jurai Siwo Metro, 2010)
AbstractArkoun finds even secularist and reformist Muslims who are still prisoners, in their discourse of the problematic thrown up by the Modernity of the Classical Age (1800-1950), imposed by the so-called revolutionary civilized Europe until at least 1950. In order to transcend this impasse, Muslims must undertake a radical double critique: western Modernity and the Islamic heritage, with the aim of transcending both, instead of just trying to come to terms with the European modernity while still prisoner to a heritage that is uncritically re appropriated. This article shows that Arkoun interpret the modernity that is based on philosophical, more than just a historical or sociological sense. Arkoun distinguish between